Conodont biostratigraphy of the middle Cambrian through lowermost Ordovician in Hunan, South China - Dong, XP; Repetski, JE; Bergstrom, SM (acta geologica sinica english edition, 2004)
Since 1985, samples with a total weight of more than 14,000 kg, mainly from three key sections in western and northwestern Hunan, South China, have been processed for conodonts. In strata older than the late. Late Cambrian paraconodonts have proved useful for stratigraphic subdivision and correlation. Thirteen conodont zones are proposed in the Middle Cambrian through lowermost Ordovician. The correlation between these zones and those of North China, western U. S.A., western Newfoundland, Canada, and Iran is discussed. In ascending order, these 13 zones are as follows: The Gapparodus bisulcatus-Westergaardodina brevidens Zone, Shandongodus priscus-Hunanognathus tricuspidatus Zone, Westergaardodina quadrata Zone, Westergaardodina matsushitai-W. grandidens Zone, Westergaardodina lui-W ani Zone, Westergaardodina cf. calix-Prooneotodus rotundatus Zone, Proconodontus tenuiserratus Zone, Proconodontus Zone, Eoconodontus Zone, Cordylodus proavus Zone, Cordylodus intermedius Zone, Cordylodus lindstromi Zone, and Cordylodus angulatus Zone (lower part). The Westergaardodina lui-W. ani and Westergaardodina cf. calix-Prooneotodus rotundatus Zones replace the Westergaardodina proligida and Westergaardodina cf. behrae-Prooneotodus rotundatus Zones, respectively, in the lowermost Upper Cambrian. Two new species (Westergaardodina lui and Westergaardodina ani) and one conditionally identified species (Westergaardodina cf. calix) are described. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000227099900003&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Geosciences, Multidisciplinary SCI(E) 41 ARTICLE 6 1185-1206 78